2019
DOI: 10.1111/agec.12497
|View full text |Cite
|
Sign up to set email alerts
|

Off‐farm work and technical efficiency on U.S. dairies

Abstract: In this study, we investigate the impact of an increase in farm households' off-farm work on technical efficiency (TE) of U.S. dairies. We present a theoretical framework that implies that an increase in farm household off-farm work decreases TE. We use two nationally-representative samples of U.S. dairies (2010 and 2005 Agricultural Resource Management Surveys) and a parametric approach (stochastic frontier analysis) to empirically test the hypothesis. Results are generally consistent with the hypothesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
1
16
1
1
Order By: Relevance
“…In other words, in addition to its risk-reducing benefits, diversification offers the opportunity to exploit the complementary potential of the farm and a more efficient distribution of the family workforce, at the same time, minimizing the economic and entrepreneurial risk [18]. Moreover, the percentage of family work is often negatively associated with efficiency [19]; different results were obtained by Sabasi et al [20] that found a negative association between the (increase in) off-farm work by the farm household and the (decrease in) the efficiency of U.S. dairies.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…In other words, in addition to its risk-reducing benefits, diversification offers the opportunity to exploit the complementary potential of the farm and a more efficient distribution of the family workforce, at the same time, minimizing the economic and entrepreneurial risk [18]. Moreover, the percentage of family work is often negatively associated with efficiency [19]; different results were obtained by Sabasi et al [20] that found a negative association between the (increase in) off-farm work by the farm household and the (decrease in) the efficiency of U.S. dairies.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…The variables considered in both 𝑥 𝑖𝑗𝑡 and 𝑧 𝑖𝑡 in Equation ( 2) and (3) are selected based on a review of related efficiency literature (Alem, Lien, Hardaker, & Guttormsen, 2019;Girma, 2019;Ma, Bicknell, & Renwick, 2019;Mareth, Scavarda, Thomé, Oliveira, & Alves, 2019;Mareth, Thomé, Scavarda, & Oliveira, 2017;Mehmood, Rong, Bashir, & Arshad, 2018;Sabasi, Shumway, & Astill, 2019;Skevas, Emvalomatis, & Brümmer, 2018). The input variables 𝒙 𝑗𝑖𝑡 ′ 𝑠 include: 𝑥 1 is farmland, defined as productive land (both owned and rented) in hectares, 𝑥 2 is labour, measured as total labour hours used on the farm, including hired labour, owners' labour, and family labour, 𝑥 3 is the number of milk cows measured as livestock units, 𝑥 4 is capital, a service flow from land and buildings estimated as 5 percent of market value plus accrual machinery hire expenses, accrual machinery repair expenses, and machinery depreciation, 𝑥 5 is accrual purchased feed measured in Kenya Shillings (KES), and 𝑥 6 is other expenses which includes breeding expenses, veterinary and medicines, and other livestock expenses (KES).…”
Section: Data and Definition Of Variablesmentioning
confidence: 99%
“…Less expensive labor-saving technologies, such as automatic take offs, udder washers, and computerized milking and feeding systems have been available for many years, but there was still relatively low take-up of these technologies in the years preceding the implementation of 287(g) policies (Khanal, Gillespie, and MacDonald 2010). 2 Sabasi, Shumway, and Astill (2019) find that smaller dairies are typically less technically efficient than large ones, and they attribute this, in part, to the fact that operators of small dairies devote more time to earning off-farm income.…”
Section: Many Of the Available Labor-saving Technologiesmentioning
confidence: 99%
“…Our second data set is the Dairy Costs and Returns Report of the ARMS, conducted every five years with surveys in 2000, 2005, and 2010. These surveys are conducted with farms randomly selected from groups of dairy farms stratified by value of sales (Sabasi, Shumway, and Astill 2019). The disadvantage of the dairy surveys is that we cannot leverage the temporal variation in the passage of 287 (g) policies.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation